2019
DOI: 10.1038/s41467-019-09287-7
|View full text |Cite
|
Sign up to set email alerts
|

Water impacts nutrient dose responses genome-wide to affect crop production

Abstract: Changes in nutrient dose have dramatic effects on gene expression and development. One outstanding question is whether organisms respond to changes in absolute nutrient amount (moles) vs. its concentration in water (molarity). This question is particularly relevant to plants, as soil drying can alter nutrient concentration, without changing its absolute amount. To compare the effects of amount vs. concentration, we expose rice to a factorial matrix varying the dose of nitrogen (N) and water (W) over a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Over the past decade, transcriptomic approaches have been employed to investigate how plants signal changes in N or W availability at the molecular level. These studies have revealed that thousands of genes are differentially expressed in response to either changes in N dose or W status, highlighting that the gene regulatory networks that govern responses to N and W are highly complex ( Vidal and Gutierrez, 2008 ; Wilkins et al , 2010 ; Sharma et al , 2018 ; Swift et al , 2019 ).…”
Section: N and W Signals Converge At The Transcriptome Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past decade, transcriptomic approaches have been employed to investigate how plants signal changes in N or W availability at the molecular level. These studies have revealed that thousands of genes are differentially expressed in response to either changes in N dose or W status, highlighting that the gene regulatory networks that govern responses to N and W are highly complex ( Vidal and Gutierrez, 2008 ; Wilkins et al , 2010 ; Sharma et al , 2018 ; Swift et al , 2019 ).…”
Section: N and W Signals Converge At The Transcriptome Levelmentioning
confidence: 99%
“…Indeed, given their central role in plant physiology, N and W have many combinatorial effects on plant phenotypes. Arguably the most important interaction is their combined effect on biomass and crop yield potential—which is only achieved when both N and W are non-limiting ( Patterson et al , 1997 ; Di Paolo and Rinaldi, 2008 ; Brueck and Senbayram, 2009 ; Shi et al , 2014 ; Swift et al , 2019 ) ( Fig. 1A ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, previous studies have shown that N nutrient dose sensing enables plants to reprogram both their gene expression patterns (8,9) as well as their phenotype, including the rate of N uptake and plant growth (10,11). However, what remains unknown are the molecular mechanisms that enable the dose of N to inform gene expression levels, and how such gene expression changes lead to dose-responsive changes in plant phenotype.…”
mentioning
confidence: 99%